Acid–base physiology over tidal periods in the mussel Mytilus edulis: size and temperature are more influential than seawater pH. Issue 1897 (20th February 2019) - Mangan, Stephanie; Wilson, Rod W.; Findlay, Helen S.; Lewis, Ceri
Abstract : Ocean acidification (OA) studies to date have typically used stable open-ocean pH and CO2 values to predict the physiological responses of intertidal species to future climate scenarios, with few studies accounting for natural fluctuations of abiotic conditions or the alternating periods of emersion and immersion routinely experienced during tidal cycles. Here, we determine seawater carbonate chemistry and the corresponding in situ haemolymph acid–base responses over real time for two populations of mussel ( Mytilus edulis ) during tidal cycles, demonstrating that intertidal mussels experience daily acidosis during emersion. Using these field data to parameterize experimental work we demonstrate that air temperature and mussel size strongly influence this acidosis, with larger mussels at higher temperatures experiencing greater acidosis. There was a small interactive effect of prior immersion in OA conditions (pHNBS 7.7/pCO2 930 µatm) such that the haemolymph pH measured at the start of emersion was lower in large mussels exposed to OA. Critically, the acidosis induced in mussels during emersion in situ was greater (ΔpH approximately 0.8 units) than that induced by experimental OA (ΔpH approximately 0.1 units). Understanding how environmental fluctuations influence physiology under current scenarios is critical to our ability to predict the responses of key marine biota to future environmental changes.